Penerapan Model Pembelajaran Problem Based Learning Pada Pelajaran Teknologi Jaringan Berbasis Luas - Erwoko, Erwoko (Civil Officium: Journal of Empirical Studies on Social Science, 2021)
This study aimed to determine the increase in student activity and learning outcomes through the implementation of the Problem Based Learning (PBL) model. This research is based on the fact that the average score of students is deficient; as many as 18 students have not completed, while 16 students have completed learning. This research is classroom action research conducted in 3 cycles. The method of data collection was carried out through observation. Data analysis was carried out by comparing the test results in cycle 1, cycle 2, and cycle 3 with descriptive techniques. The results of this study indicate that the application of the Problem Based Learning model assisted by Edmodo in the subject of Animation can improve student learning outcomes. In the first cycle, it was 47%, in the second cycle, it increased to 74%, then in the third cycle it increased to 88%, so with these data, it can be concluded that the achievement of the research success criteria for student learning outcomes has been achieved. Thus, it can be concluded that class IX students' learning outcomes and learning activities in the Lua-Based Network Technology lesson at SMKN 1 SEMENDAWAI SUKU III have increased.